KEKUATAN HUKUM AKTA PERDAMAIAN YANG DIBUAT DIHADAPAN NOTARIS DAN PUTUSAN AKTA PERDAMAIAN PENGADILAN - Firmansyah, Yanuar Rozi (Jurnal Cakrawala Hukum, 2017)
The making of authentic deed is one of notary authority in making deed. The realization of the verdict of thepeace deed which obtains the force of law remains voluntary and execute. Deed of peace of civil case in court related to notary authority in making peace deed. The legal power of a peace deed made by a notary and a verdict of a peace deed of the court in a land rights sale disposal dispute. Notaryâ€™s authority to make a peace deed to the land rights sale disputes related to the decision of a permanent law enforcement law deed. Thenotarial deed of peace has three types of proof, in the form of external proof power, the power of formal proof, the power of material proof. A peace deed made before a notary has the power of an ordinary judgeâ€™s verdict which has had a permanent legal force. Notary is required to register in court through the process of lawsuit. If during a peace deed made before a notary public is not registered in court then the peace deed is still in theÂ form of agreement only. DOI: https://doi.org/10.26905/idjch.v8i2.2114